Nobody does it better : a Gossip Girl novel - Von Ziegesar, Cecily (Little, Brown, 2005)
Scandal abounds as the uptown girls take "time to shop, drink, eat, and make merry," winding up their days as Constance Billard students with a Senior Spa Day that is crashed by The Raves rock group and assorted other guys.